Growth and spectral analysis of stacked quantum dots for broadband superluminescent diodes - Park, Moon Ho; Park, Sung Jun; Song, Jin Dong; Choi, Won Jun; Kim, Kwang Woong; Lim, Ju Young; Lee, Yoo Jong; Park, Jung Ho (KOREAN PHYSICAL SOC, 2013)
Stacks of different quantum dot (QD) structures were adopted and characterized for broadband superluminescent diodes (SLDs). Each QD structure in the stacked QD structures exhibited a unique peak in the photoluminescence (PL) spectrum, showing ground-state peaks of similar to 1272, similar to 1185 and similar to 1090 nm for InGaAs-capped InAs QDs, InAs QDs, and InGaAs QDs, respectively. Two SLD structures, one with the stack of InGaAs-capped InAs QDs, InAs QDs, and InGaAs QDs and the other with the stack of InGaAs-capped InAs QDs and InAs QDs, were grown and fabricated into devices. The SLDs with a stack of three different QD structures and with a stack of two different QD structures showed spectral bandwidths of 173.6 nm and 188.2 nm, respectively, in the electroluminescence (EL) measurements. The larger spectral bandwidth of the SLD with three different QD structures is thought to be due to the addition of the short-wavelength-emitting InGaAs QD structure. We analyzed the sub-peaks in the EL spectra of the SLD structures and suggested the stacking of QD structures to get broadband SLDs.
Keywords: WAVELENGTH; 1.3-MU-M; EPITAXY